2012
DOI: 10.5432/jjpehss.11097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grip position and pitching speed on baseball bat swing

Abstract: AbstractA study was conducted to investigate diŠerences in bat swing between the use of long and short bat grip positions. Fifteen male baseball players were videotaped at 250 Hz using two high-speed video cameras while they were batting balls placed on a batting tee and pitched at 80, 100, and 120 km/h by a pitching machine. The bat head and grip end were digitized, and the three-dimensional coordinates were calculated using the direct linear transformation (DLT) method. Bat head velocity at impact employing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 7 publications
1
7
1
Order By: Relevance
“…The batter performed the swing with the chock-up grip position (hands oneˆst above the normal grip) only in the third swing. This was referred to as the chock-up grip position by Kawabata and Ito (2012). The participants were required to swing as fast as possible.…”
Section: Experimental Task Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…The batter performed the swing with the chock-up grip position (hands oneˆst above the normal grip) only in the third swing. This was referred to as the chock-up grip position by Kawabata and Ito (2012). The participants were required to swing as fast as possible.…”
Section: Experimental Task Proceduresmentioning
confidence: 99%
“…Katsumata and Kawai (1996) reported that a baseball swing is executed after the batter stepsˆrmly on the ground with the front leg. Moreover, Kawabata and Ito (2012) deˆned the time to peak GRF in front leg as swing initiation. Therefore, the signiˆcant delay in the time to peak GRF in the third swing in the present study indicates the delay of the swing initiation.…”
Section: Muscle Activation Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations